2014
DOI: 10.3892/mco.2014.444
|View full text |Cite
|
Sign up to set email alerts
|

Benefits from adjuvant intraoperative radiotherapy treatment for gastric cancer: A meta-analysis

Abstract: The benefits of adjuvant intraoperative radiotherapy (IORT) for resectable gastric cancer have been extensively studied, but data on the survival rate remains equivocal. A meta-analysis was performed of the studies involving the use of IORT for resectable gastric cancer using web-based databases. Hazard ratios (HRs) describing the impact of adjuvant IORT on the overall survival (OS) rate and locoregional control were extracted directly from the original studies or calculated from survival curves. A meta-analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
1
3
0
1
Order By: Relevance
“…Complications were similar between the IOeRT group and control group (OR = 1.15; 95% CI 0.77-1.72; P = 0.50). The results supported findings observed in a previous metaanalysis showing a statistically significant loco-regional control benefit with the addition of IOeRT in patients with resectable gastric cancer and the indication that IOeRT may provide promising results on overall survival for the subgroup of patients with stage III disease [30].…”
Section: Intraoperative Electron Radiation Therapy (Ioert) In Esophag...supporting
confidence: 89%
“…Complications were similar between the IOeRT group and control group (OR = 1.15; 95% CI 0.77-1.72; P = 0.50). The results supported findings observed in a previous metaanalysis showing a statistically significant loco-regional control benefit with the addition of IOeRT in patients with resectable gastric cancer and the indication that IOeRT may provide promising results on overall survival for the subgroup of patients with stage III disease [30].…”
Section: Intraoperative Electron Radiation Therapy (Ioert) In Esophag...supporting
confidence: 89%
“…ESCC is the third most common cancer in South African men [ 53 , 54 ]. Although promising progress has been attained in treating esophageal cancer, it responds poorly to chemotherapeutic drugs and the mortality still remains high [ 51 , 55 , 56 , 57 , 58 , 59 ]. Surgery, chemotherapy and radiotherapy are the most widely-used treatment methods but about half of advanced esophageal cancer cases result in recurrence and patients normally succumb to resistant disease [ 60 , 61 , 62 , 63 , 64 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides direct cytotoxic effects, IORT alters the tumor microenvironment and blunts angiogenesis, thereby hindering further tumor growth (20). The incorporation of IORT into surgery prolongs OS in stage 3 GCa patients and signi cantly improves locoregional control (21). Furthermore, studies have found no increase in surgical complications when using IORT for GCa (22).…”
Section: -Discussionmentioning
confidence: 99%